2015
DOI: 10.1186/s11671-015-0761-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of carbyne: experiment and simulations

Abstract: The results of the high-field technique for obtaining and testing the carbyne strength in situ are presented. By using molecular dynamics simulation and ab initio calculations, a comprehensive analysis of the results is executed. High-field technique for experimental measurement of the carbyne strength in situ is briefly described. It is shown that the technique used gives a lower estimation for strength of carbyne, which equals 251 GPa at T = 77 K. This value is close to the strength 7.85 nN (250 GPa) of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Experimental evidence on strength of this object is obtained just recently [3,36]. It was ascertained that carbyne strength is more than 2 times greater than strength of graphene.…”
Section: Strength Of 2d-and 1d-crystalsmentioning
confidence: 93%
See 1 more Smart Citation
“…Experimental evidence on strength of this object is obtained just recently [3,36]. It was ascertained that carbyne strength is more than 2 times greater than strength of graphene.…”
Section: Strength Of 2d-and 1d-crystalsmentioning
confidence: 93%
“…Most clearly this effect can be demonstrated for allotropic forms of carbon. Thus, the strength of defect-free 3-D Crystal (diamond) is 95 GPa [39], of 2D-crystal (graphene) -130 GPa [2] and of 1D-crystal (carbyne) -more than 270 GPa [36]. To explain these regularities, strengths of atomic bonds in diamond, graphene and carbyne were estimated in (Fig.…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…However, its weakness in a compression and chemical instability requires some kind of confinement, usually performed with carbon nanotubes or graphene. Experimentally, carbyne appears to be the strongest material [20] having the strength of 251 GPa at 77 K when attached to graphene. A famous 2D-modification of graphene itself has more than two times less value-that of 130 GPa.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…On its own, carbyne has also been investigated for applications like mechanical energy harvesting [27], super capacitors [28] and potential batteries [29], but not for any kind of composite materials. To date, carbyne's theoretically modeled and estimated superior strength and elastic modulus have been reported in various studies [30][31][32][33], which is much higher than any known material, including other forms of fullerene and even diamond. It is the strongest material in the world with a reported experimental estimation strength of 270 GPа (at 5 K) and 251 GPa (at 77 K), more than twice the strength of graphene (130 GPа) [31].…”
Section: Introductionmentioning
confidence: 99%
“…To date, carbyne's theoretically modeled and estimated superior strength and elastic modulus have been reported in various studies [30][31][32][33], which is much higher than any known material, including other forms of fullerene and even diamond. It is the strongest material in the world with a reported experimental estimation strength of 270 GPа (at 5 K) and 251 GPa (at 77 K), more than twice the strength of graphene (130 GPа) [31]. In another study, carbyne has shown to be about twice stiffer than the stiffest known materials and has an unrivalled specific strength of up to 7.5 x 107 Nm/kg, requiring a force of ∼10 nN to break a single atomic chain under tensile load [33].…”
Section: Introductionmentioning
confidence: 99%